2018
DOI: 10.1002/2017gc007300
|View full text |Cite
|
Sign up to set email alerts
|

Tuffaceous Mud is a Volumetrically Important Volcaniclastic Facies of Submarine Arc Volcanism and Record of Climate Change

Abstract: The inorganic portion of tuffaceous mud and mudstone in an oceanic island arc can be mostly volcanic in origin. Consequently, a large volume of submarine volcaniclastic material is as extremely fine‐grained as products of subaerial eruptions (<100 µm). Using results of IODP Expedition 350 in the Izu rear arc, we show that such material can accumulate at high rates (12–20 cm/k.y.) within 13 km of the nearest seamount summit and scores of km behind the volcanic front. The geochemistry of bulk, acid‐leached mud, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 119 publications
0
24
0
Order By: Relevance
“…Many drilling cruises have focused on the Izu-Bonin forearc and volcanic front (e.g., Fryer & Pearce, 1992;Reagan et al, 2017;Taylor et al, 1992), but Site U1437 represents the first drilling within the rear-arc region (Figure 1). In three consecutive cored holes, the JOIDES Resolution ultimately drilled down to 1,806.4 meters below seafloor (mbsf), through at least 15 Myr of volcaniclastic stratigraphy, with tephra and other volcano-derived materials alternating with thick successions of tuffaceous mud (Figure 2; Tamura et al, 2015;Gill et al, 2018;Schmitt et al, 2017). The core was subdivided into seven lithostratigraphic units, based on the relative proportion of mud to discrete ash or tephra.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…Many drilling cruises have focused on the Izu-Bonin forearc and volcanic front (e.g., Fryer & Pearce, 1992;Reagan et al, 2017;Taylor et al, 1992), but Site U1437 represents the first drilling within the rear-arc region (Figure 1). In three consecutive cored holes, the JOIDES Resolution ultimately drilled down to 1,806.4 meters below seafloor (mbsf), through at least 15 Myr of volcaniclastic stratigraphy, with tephra and other volcano-derived materials alternating with thick successions of tuffaceous mud (Figure 2; Tamura et al, 2015;Gill et al, 2018;Schmitt et al, 2017). The core was subdivided into seven lithostratigraphic units, based on the relative proportion of mud to discrete ash or tephra.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…Age data with arrows are U-Pb zircon ages from Schmitt et al (2018). The depth of samples of this study (including the samples of Sato et al 2020), and the mud samples of Gill et al, (2018) are shown on the left side of the figure. The samples with Nb/Yb ratio of <0.2, 0.2-0.7, and >0.7 are classified as VF-type, Rift-type, and RASC-type.…”
Section: Major and Trace Elementsmentioning
confidence: 99%
“…Tuffaceous mud and mudstone with intercalated ashes and volcaniclastics characterize the uppermost 1,320 m, comprising Lithological Units I through V, with only two comparatively short intervals (Units II and IV) in which fine volcaniclastics dominate. Locally derived volcanic components generally make up 70–100% of the mud fraction, although this drops to 20–50% in intervals deposited during Pleistocene glacials in the upper part of Unit I, where continentally derived hemipelagic muds dominate (Gill et al, ; Kars et al, ). Unit VI, from 1,320 to 1,460 mbsf, exhibits a coarser volcaniclastic input and a reduced mudstone component than the overlying mud‐dominated lithology of Units I through V. Mudstone is absent from the underlying Unit VII, which extends to the bottom of hole.…”
Section: Introductionmentioning
confidence: 99%